2013
DOI: 10.2458/azu_js_rc.55.16269
|View full text |Cite
|
Sign up to set email alerts
|

A Study of KF3- Attenuation in an RFQ Gas Cell for 41Ca AMS

Abstract: Guided by simulations using SIMION 8.1, a series of modifications were made to an experimental version of an Isobar Separator for Anions (ISA). The resulting improved version of the ISA provides a means of re-energizing the ions after they are cooled by gas collisions as they pass through the gas-filled radiofrequency quadrupoles (RFQ), and also provides higher transmission efficiencies. Reinvestigation of the separation of CaF 3  and KF 3  with this refined apparatus resulted in a better balance between iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…Other system details and experimental procedures were identical to those described earlier. [13][14][15][16] RESULTS AND DISCUSSION Figure 2 shows the Hf and W beams transmitted through the test isobar separator containing varying concentrations of NO 2 gas. NO 2 is both an electronegative gas and a radical.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Other system details and experimental procedures were identical to those described earlier. [13][14][15][16] RESULTS AND DISCUSSION Figure 2 shows the Hf and W beams transmitted through the test isobar separator containing varying concentrations of NO 2 gas. NO 2 is both an electronegative gas and a radical.…”
Section: Methodsmentioning
confidence: 99%
“…Detailed descriptions of the experimental apparatus and the ion energy evaluation procedures by SIMION simulations are given elsewhere. [16] A simulation with the actual experimental conditions used for the HfF 5 À /WF 5 À studies is shown in Fig. 1.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations